One-Pot Hydrothermal Synthesis of MoS2/Zn0.5Cd0.5S Heterojunction for Enhanced Photocatalytic H2 Production - Li, Xinru; Xue, Fei; Li, Naixu; Wei, Xukai; Liu, Hui; Zhou, Jianchen; Lyu, Bin; Liu, Maochang (Frontiers in Chemistry, 2020)
A series of MoS2/Zn0.5Cd0.5S heterojunctions have been prepared via a mild one-pot hydrothermal method based on the optimization of composition content of primary photocatalyst. The photocatalysts demonstrated significantly improved visible-light-driven photocatalytic activity toward H2 evolution from water without using any noble metal cocatalyst. Among the as-prepared composites, 0.2% MoS2/Zn0.5Cd0.5S shows the best performance. The highest H2-evolution rate reaches 21 mmol·g-1·h-1, which is four times higher than that of pure Zn0.5Cd0.5S. The apparent quantum efficiency is about 46.3 % at 425 nm. The superiority is attributed to the tight connection between MoS2 and Zn0.5Cd0.5S by this facile one-step hydrothermal synthesis. As a result, the formation of the heterostructure introduces built-in electric field at the interface that facilitates vectorial charge transfer. More specifically, photogenerated electrons transfer to MoS2 to conduct proton reduction, while the holes are retained on the surface of Zn0.5Cd0.5S to react with the sacrificial reagents. Moreover, the composite presents improved stability without notable activity decay after several cycled tests.